“Stay Tuned”: Inter-Individual Neural Synchronization During Mutual Gaze and Joint Attention - Saito, Daisuke N.; Tanabe, Hiroki C.; Izuma, Keise; Hayashi, Masamichi J.; Morito, Yusuke; Komeda, Hidetsugu; Uchiyama, Hitoshi; Kosaka, Hirotaka; Okazawa, Hidehiko; Fujibayashi, Yasuhisa; Sadato, Norihiro (Frontiers in Integrative Neuroscience, 2010)
Eye contact provides a communicative link between humans, prompting joint attention. As spontaneous brain activity may have an important role in coordination of neuronal processing within the brain, their inter-subject synchronization may occur during eye contact. To test this, we conducted simultaneous functional MRI in pairs of adults. Eye contact was maintained at baseline while the subjects engaged in real-time gaze exchange in a joint attention task. Averted gaze activated the bilateral occipital pole extending to the right posterior superior temporal sulcus, the dorso-medial prefrontal cortex, and bilateral inferior frontal gyrus. Following a partner’s gaze towards an object activated the left intraparietal sulcus. After all task-related effects were modeled out, inter-individual correlation analysis of residual time-courses was performed. Paired subjects showed more prominent correlations than non-paired subjects in the right inferior frontal gyrus, suggesting that this region is involved in sharing intention during eye contact that provides the context for joint attention.